#TITLE_ALTERNATIVE# - IMRAN HAMID (NIM 23298508); Pembimbing: Dr.Ir. Pekik Argo Dahono, MUHAMMAD
Configurations of Two Winding Interphase Transformers (2-I1'Ts) for paralleling high current low voltage rectifiers are analyzed to meet optimum configuration in aspect of number and total VA rating required for a number of N inputs. Then, the rectifier's current ripples of these configurations are analyzed. The research takes a case study for paralleling three one-phase rectifiers from secondary side of three-phase transformer. Analysis and experiment show that the combinatorial shunt configuration is the most advantageous in the aspect of the total rating, but the most disadvantageous in the aspect of number of 2-IPTs. In the aspect of number of 2-IPTs, secondary loop, cyclic cascade and cyclic shunt are the most advantageous configurations., The experiment is also show that the positive polarity of 2-IPTs gives high current ripple on the phase side and low ripple on the load side but gives current discontinuity on phase side, on the contrary, the negative polarity gives low current ripple on the phase side and high ripple on the load side but its give continuity of current on phase side.